Nursing perceptions of medication administration practices, reasons for errors and reporting of errors in a tertiary care hospital, Bangalore - Mahesh, Meenakshi; I., Hajira Saba; Gopi, Arun (International Journal Of Community Medicine And Public Health, 2017)
Background: Nurses administer drugs directly to patients and they are the last link in the safe medication administration chain. Due to the increased acuity of patients they serve, and decrease in the resources available to ensure safe practice, there are more chances of errors to occur. The study was thus taken up to describe their perspectives towards medication administration practices, sources and reporting of errors. Methods: Study was conducted on nursing staff of Vydehi Hospital, Bangalore, India. The study was cross sectional type of study which has taken one month duration to complete. By simple random sampling, 199 nurses were selected and interviewed. They were administered a semi structured questionnaire after obtaining oral consent and assuring complete anonymity. The data was analyzed using Chi-square, Annova and principal component analysis, SPSS version 21. Results: Among the nurses, 97% always checked the patient’s file for medication details before administration, 45.7% never prepared medications for more than 2 patients at a time and 78.4% always checked the expiry date before administering the drug. 83.9% nurses always practice sterile conditions for administering intramuscular and intravenous medicines. Conclusions:The common causes of errors were mislabelled drugs and names/labels of medicines which look alike. 66.3% of nurses always reported the errors. There was a significant association between the years of experience and the lack of cross checking with another nurse before administering of heparin and insulin and checking composition of medicines.